Financial management, savings and investment behavior and financial well-being of working women in the public sector - Sabri, Mohamad Fazli; Syahrul Reza, Teuku; Wijekoon, Rusitha (Resista VIkaliana, 2020)
Women have made an amazing progress personally, financially, and professionally however, with regards to the field of finance, an extensive effort to be done to become well performers comparing to the men. Therefore, women must begin understanding, and thinking the significance of money, savings, and its investment perspectives to overcome critical circumstances at any phase of their lives. Therefore, the major objective of this research is to investigate the relationships among financial management, savings and investment behavior, and financial well-being (FWB) of working women in the public sector in Malaysia. A sum of 722 respondents were selected using the multi-stage random sampling method in Malaysia. According to the financial status of working women, 39.2% felt that their assets were more than their debt, and 44.3% was said that their salary was sufficient to meet only their basic requirements. Furthermore, more than 80% of the respondents were followed good financial management practices such as, keeping updated records of the expenses, planning the expenses, doing investments monthly, keeping the loan payment on schedule, settling all the bills on time, and maintaining a savings account. Moreover, it also showed that Malaysian working women have good financial management practices which are indicated by their abilities in performing the savings and investment behaviors to manage their surplus money wisely in order to achieve higher FWB levels. Further, this study was detected some specific financial challenges that Malaysian public sector working women meet over their lifetime, and offered possible solutions for the present and future.